Beyond Ideology.Trade and Finance between Argentina and Venezuela - Roark, Mariano (2010)
This article offers an analysis of bilateral relations between Argentina and Venezuela during the period 2003-2008. The overall objective is to offer an approximation of how the countries have come closer together in matters of economic development during the years cited, establishing a general analysis of opportunities and challenges that the strengthening of ties implies for the countries involved.